Plasma Process. Polym. 10∕2013. Issue 10 (9th October 2013) - Duday, David; Clément, Franck; Lecoq, Elodie; Penny, Christian; Audinot, Jean‐Nicolas; Belmonte, Thierry; Kutasi, Kinga; Cauchie, Henry‐Michel; Choquet, Patrick
<x xml:space="preserve">Abstract</x> Cover: Superposed NanoSIMS‐AFM images showing enrichment in 18O, as indicated by orange‐red spots, coming directly from the discharge on the plasma treated bacteria deposited on a polycarbonate filter. 18O fixation on bacteria is high and not homogeneous in Ar‐N2‐O2 microwave afterglow. Further details can be found in the article by David Duday et. al. on page 864. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>